Designing an indigenous treatment model and evaluating its effectiveness on the symptoms of post-traumatic stress disorder in women and men who survived the Kermanshah earthquake - Khosravi, Tareq; Gudarzi, Mahmoud; Ahmadian, Hamzeh (Applied Family Therapy Journal (AFTJ), 2022)
The current research was conducted with the aim of designing a native treatment model and evaluating its effectiveness on the symptoms of post-traumatic stress disorder. Method: The current research population includes all the women and men who survived the Kermanshah earthquake in the cities of Salas Babajani and Sarpol-Zahab, and after obtaining the codes and compiling and implementing the local treatment model, two experimental and proof groups, 10 people each, a total of 20 people by sampling method were selected and randomly assigned to two experimental and control groups. The post-traumatic stress disorder questionnaire was used for the implementation of the present study. The treatment model consists of 15 sessions that were taught to the clients during fifteen weeks. Each training session of the indigenous treatment model (researcher-made) lasted about 100 minutes. Results: The findings showed that re-experience symptoms (P=0.001, F=12.15), avoidance symptoms (P=0.001, F=17.65), and arousal symptoms (P=0.001, F=11.18) were significant at the level of 0.01. In the experimental group, the mean scores of symptoms of post-traumatic stress disorder decreased in post-test and follow-up stages compared to the control group. The mean difference between post-traumatic stress disorder symptoms in post-test and follow-up stages was 0.05. This finding shows that changes in the mean scores of symptoms of post-traumatic stress disorder remained paparaja after the end of the treatment period. Conclusion: It can be concluded that this method of treatment is effective for people suffering from post-traumatic stress disorder.